TUFANDAN ÖNCE HİKÂYESİNDE OYUN VE AFET ARASINDA KASABA HALKININ DRAMI - (:unkn) unknown (My University, 2014)
Geçmişten bugüne dinî ve mitik inanışa dayanan tufan hadisesi edebî me- tinlerde önemli bir yer tutar. Tufan hadisesinin işlenişi yazarların kaynaklarına göre değişiklik gösterse de cezalandırma, arınma ve yeniden doğuş bu eserlerde ortak motif olarak geçer. Modern Türk edebiyatının önemli yazarlarından Mustafa Kutlunun Tuf andan Önce hikâyesinde Nuh Tufanını imleyen birçok metaforun eserin dokusuna ustaca yerleştirildiği görülür. Yazarın kaynaklarının İslâmi olması dolayısıyla, eserdeki sembolik unsurlar, göndermeler ve anıştırmaların Kuran-ı Kerimdeki kıssa, anekdot ve ayetlerle ilintili olduğu görülür. Başka eserlerinde de siyaset ve toplum ilişkisine yer veren yazar, Tuf andan Önce hikâyesinde siyasi yozlaşmayı ayrıntılı olarak işler; bir Anadolu kasabasındaki durumla Nuh Tufanı arasında benzerlik kurar. Bu çalışmada Tuf andan Önce hikâyesi siyaset-toplum ilişkisi bağlamında değerlendirilip Anadolu kasabasındaki durumla Hz. Nuhun kavmi ve tufan hadisesi arasındaki benzerlikler üzerinde durulmuştur.

: From past to present, the flood narrative, based upon religious and mythical beliefs, has always occupied an important place in literary works. Even though the exploration of the flood motif differs in accordance with the sources of the writers; punishment, salvation, and rebirth are common motifs in these works. In the story Tufandan Önce by Mustafa Kutlu, one of the dis- tinguished writers in Turkish literature, it is seen that many metaphors referring to Noah s flood are employed skillfully. Due to the fact that the writer s sources are Islamic, it is seen that symbolic elements, implications and allusions in his work are related to stories, anecdotes and verses of Holy Quran. The writer, who deals with the relationship between politics and society in his other works as well, profoundly reveals political corruption in Tufandan Önce. He compa- res the situation in an Anatolian town to that of the Noah s people. This paper, firstly, deals with the relationship between politics and society in Tufandan Önce and secondly, aims to reveal the similarities between the social context in the Anatolian town and that of Noah s people with references to the flood.
THE PEOPLE OF TOWN S DRAMA, BETWEEN THE PLAY AND DISASTER IN THE SHORT STORY TUFANDAN ÖNCE [BEFORE THE GREAT FLOOD]
Keywords: Kültürel Çalışmalar